CREATIVE BIBLIOPHILISM IN LITHUANIA (1930–1940) - BRAZIŪNIENĖ, ALMA (Knygotyra, 2015)
The article deals with the bibliophilism in Lithuania in 1930–1940. On the basis of publications, archyve material and oral history sources some aspects of the creative self-expression of bibliophiles are analysed (bibliophiles sensu stricto and book lovers). The analysis of private libraries of the most prominent bibliophiles and book lovers of that period (V. Biržiška’, A. Janulaitis’, K. Jablonskis’, V. Steponaitis’, P. Jakštas’, Vaižgantas’, P. Galaunė’, V. Burkevičius’, V. Daumantas’, A. Mošinskis’, J. Šaulys’ and others) leads to a conlusion that some favourable conditions for the spread of bibliophilism appeared in Lithuania before the II World War. The attention of the cultural politic of Lithuania of that time was focused away from the elite culture and was concentrated to the folk culture, but an elite stile of bibliophilism and the lifestyle of bibliophiles themselves was actualy cultivated too. The members of the Society of 27 Book Lovers, which functioned in Kaunas in 1930–1940, had started bibliophilic activities in line with Western bibliophilic images. The historical distance between actual folk culture and aristocratic culture caused that Lithuanian bibliophilic life of that time and activity of the Society of 27 Book Lovers were very secluded.